Validity of an upper-body-mounted accelerometer to measure peak vertical and resultant force during running and change-of-direction tasks - Wundersitz, D. W. T.; Netto, K. J.; Aisbett, B.; Gastin, P. B. (Sports Biomechanics, 2013)
This study assessed the validity of a tri-axial accelerometer worn on the upper body to estimate peak forces during running and change-of-direction tasks. Seventeen participants completed four different running and change-of-direction tasks (0°, 45°, 90°, and 180°; five trials per condition). Peak crania-caudal and resultant acceleration was converted to force and compared against peak force plate ground reaction force (GRF) in two formats (raw and smoothed). The resultant smoothed (10 Hz) and crania-caudal raw (except 180°) accelerometer values were not significantly different to resultant and vertical GRF for all running and change-of-direction tasks, respectively. Resultant accelerometer measures showed no to strong significant correlations (r = 0.00-0.76) and moderate to large measurement errors (coefficient of variation [CV] = 11.7-23.9%). Crania-caudal accelerometer measures showed small to moderate correlations (r = - 0.26 to 0.39) and moderate to large measurement errors (CV = 15.0-20.6%). Accelerometers, within integrated micro-technology tracking devices and worn on the upper body, can provide a relative measure of peak impact force experienced during running and two change-of-direction tasks (45° and 90°) provided that resultant smoothed values are used.